Nationalism, Patriotism, and Legitimation of the National Social Systems - Vargas Salfate, Salvador (2020)
In this article, we test if national identification is associated with legitimation of the national social systems based on the main tenets of social identity theory. Specifically, we distinguish between patriotism and nationalism to argue that the strongest predictor should be nationalism because it entails a sense of superiority over other countries. In addition, we test if this association is more pronounced in high-status groups considering that national identity is hierarchically constructed. In two studies conducted in Chile and Peru, we found partial support for these hypotheses. Specifically, nationalism was a significant predictor of system justification and perception of meritocracy after accounting for different theoretically relevant covariates, and this association was stronger among high-status groups.